Application of a Java-based framework to parallel simulation of large-scale systems - Niewiadomska-Szynkiewicz, Ewa; Żmuda, Maciej; Malinowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Large-scale systems, such as computer and telecommunication networks, complex control systems and many others, operate in inherently parallel environments. It follows that there are many opportunities to admit parallelism into both the algorithm of control implementation and simulation of the system operation considered.
Keywords: parallel computations; simulation; large-scale systems; computer systems; computer-aided system design